(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The aim of this study was to evaluate the effect of fluoride on the ultrastructure of skeletal muscle. Wistar albino rats were treated with 300 and 600 mg NaF/ kg bw/day respectively, for 40 days . Group I (Control) was given double distilled water ml/kg bw/day orally for the same period. In control rats, the sarcoplasm was filled with myofibrils and some mitochondria. The sarcomeres showed sarcoplasmic reticulum surrounded by Z- line, A and I-bands. The middle of the sarcomere was marked by M-line situated within lighter H-band. Oval myonucleus with finely dispersed chromatin throughout the nucleoplasm was present. In rats treated with 300 mg NaF/ kg bw/day skeletal muscle showed disorganized myofibrils and disruptions in the continuity of plasma membrane. The undulating sarcolemma and many small electron-lucent vacuoles in the myofibers were noticed. The myofibrils showed disturbed contractile structure with loss of sarcomere organization and indistinguishable. A-band, I-band , and irregular and distorted Z-line with disruption of myofilaments. Irregularly shaped markedly shrunken myonuclei with clumped and marginated chromatin were prominent. The cristae rich mitochondria were larger than those in control. The hypercontraction of myofilaments and mitochondrial swelling were observed in rats given 600 mg NaF/ kg bw/day. The sarcoplasmic reticulum was irregularly dialated forming large electron-lucent areas. The myofibrilar pattern could no longer be distinguished . There was loss of integrity of the basal lamina and plasma membrane, and inflammatory cells were present around the damaged site.